2021
DOI: 10.5194/ms-12-109-2021
|View full text |Cite
|
Sign up to set email alerts
|

Research on the influence of air-gap eccentricity on the temperature field of a motorized spindle

Abstract: Abstract. The air-gap state between the stator and rotor is an important indicator to measure the performance of a motorized spindle. It affects the temperature field distribution of the motorized spindle and the machining accuracy of the mechanical parts. Since the accurate thermal model is the basis of the research on the temperature field distribution of the motorized spindle, in this paper, firstly, the mechanical loss, electrical loss and magnetic loss of the motor under different air-gap eccentricities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Cao, Y. et al [15] analyzed the loss and temperature of the hybrid magnetic bearings (HMB), and the results showed that the loss of HMB is mainly distributed in the rotor part, and the temperature of the rotor part is obviously higher than that of the stator part. Li et al [16] established the thermal model of the motorized spindle and simulated the steady-state temperature field of the motorized spindle by using ANSYS. Zhai et al [17] established the prediction models of iron loss and copper loss for magnetic bearings and BLDCM and determined the loss coefficients of iron core by measured loss curves at different frequencies.…”
Section: Of 20mentioning
confidence: 99%
“…Cao, Y. et al [15] analyzed the loss and temperature of the hybrid magnetic bearings (HMB), and the results showed that the loss of HMB is mainly distributed in the rotor part, and the temperature of the rotor part is obviously higher than that of the stator part. Li et al [16] established the thermal model of the motorized spindle and simulated the steady-state temperature field of the motorized spindle by using ANSYS. Zhai et al [17] established the prediction models of iron loss and copper loss for magnetic bearings and BLDCM and determined the loss coefficients of iron core by measured loss curves at different frequencies.…”
Section: Of 20mentioning
confidence: 99%
“…where n is total number of discrete disks, f is friction force of the system, T is component of electromagnetic force transmitted in the axial direction, Q is shear force, F n and M n are external force and torque of the system, respectively, E is the elastic modulus, C i is the damping of the bearing inner ring, C b is the damping of the bearing ball, I is the rotational inertia of y axis, and J is the rotational inertia of z axis. The Lagrangian energy method iterative equation is given in equation (49), 5,13,14 d dt…”
Section: Dynamic Model Of Ceramic Angular Contact Bearingmentioning
confidence: 99%
“…Liu et al 12 studied the axial vibration of high-speed motorized spindle, and established a high-speed motorized spindle rotor-bearing dynamics model using the finite element method and analyzed the inherent characteristics of the system. Li et al 13 conducted a theoretical analysis and experimental study with the nonlinear dynamics of rotor-bearing system, analyzed the whole system with bifurcation diagram, waterfall diagram, and Poincaré diagram. Xi et al 14 established a nonlinear dynamics model of a five-degree-of-freedom angular contact ball-axis rotor bearing system with improved ball bearing dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al employed ANSYS software to study influences of the air-gap state between the stator and rotor of a motorized spindle on the steady-state thermal deformation of the motorized spindle. 3 Xu and Fan combined the finite element method and digital twinning to improve the simulation accuracy for thermal errors of a motorized spindle by mapping and modifying the thermal boundary conditions including the thermal contact resistance. 4 Deng et al established a coupling analysis model for the spindle-vertical column system of a machine tool using the finite element software and obtained key thermal properties of the model, including the thermal equilibrium time.…”
Section: Introductionmentioning
confidence: 99%